Cardiac Stroke Volume Index Is Associated With Early Neurological Improvement in Acute Ischemic Stroke Patients - Miller, Joseph; Chaudhry, Farhan; Tirgari, Sam; Calo, Sean; Walker, Ariel P.; Thompson, Richard; Nahab, Bashar; Lewandowski, Christopher; Levy, Phillip (Frontiers in Physiology, 2021)
Early neurological improvement as assessed with the NIH stroke scale(NIHSS) at 24 hours has been associated with improved long-term functional outcomes following acute ischemic stroke(AIS). Cardiac dysfunction is often present in AIS, but its association with outcomes is incompletely defined. We performed a pilot study to evaluate the association between noninvasively measured cardiac parameters and 24-hour neurological improvement in prospectively enrolled patients with suspected AIS who presented within 12 hours of symptom-onset and had an initial systolic blood pressure>140 mm Hg. Patients receiving thrombolytic therapy or mechanical thrombectomy were excluded. Noninvasive pulse contour analysis was used to measure mean arterial blood pressure(MAP), cardiac stroke volume index(cSVI), cardiac output(CO) and cardiac index(CI). Transcranial Doppler recorded mean middle cerebral artery flow velocity(MFV). We defined a decrease of 4 NIHSS points or NIHSS≤1 at 24-hours as neurological improvement. Of 75 suspected, 38 had confirmed acute ischemic stroke and did not receive reperfusion therapy. Of these, 7/38(18.4%) had neurological improvement over 24 hours. MAP was greater in those without improvement(108, IQR 96-123 mm Hg) vs those with(89, IQR 73-104 mm Hg). cSVI, CO, and MFV were similar between those without and with improvement: 37.4(IQR 30.9-47.7) vs 44.7(IQR 42.3-55.3) ml/m2; 5.2(IQR 4.2-6.6) vs 5.3(IQR 4.7-6.7) mL/min; and 39.9(IQR 32.1-45.7) vs 34.4(IQR 27.1-49.2) cm/s, respectively. Multivariate analysis found MAP and cSVI as predictors for improvement(OR 0.93, 95%CI 0.85-0.98 and 1.14, 95%CI 1.03-1.31). In this pilot study, cSVI and MAP were associated with 24-hour neurological improvement in AIS.